2023
DOI: 10.1097/hep.0000000000000575
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma reduced, HBsAg loss increased, and survival improved after finite therapy in hepatitis B patients with cirrhosis

Wen-Juei Jeng,
Rong-Nan Chien,
Yi-Cheng Chen
et al.

Abstract: Background & Aims: Long-term nucleos(t)ide analogue (Nuc) treatment can reduce hepatocellular carcinoma (HCC) in patients with hepatitis B virus (HBV)-related cirrhosis (HBV-LC). Earlier small cohort studies showed a comparable 5-year incidence of HCC in hepatitis B e antigen (HBeAg)-negative HBV-LC patients who stopped and those continued Nuc therapy. This study aimed to validate these findings using a large cohort with 10-year follow-up. Approach & Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…We appreciate Dongelmans et al 1 for their comments and the opportunity for clarification and further discussion. The beneficial findings of our study 2 are indeed beyond expectation but not contradictory to the current paradigm. Before end-of-therapy, finite-group patients had also enjoyed the benefits of the current paradigm, including immune restoration and reversal of hepatic fibrosis/cirrhosis during 1–5 years of nucleos(t)ide analog (Nuc) therapy 3 .…”
supporting
confidence: 46%
See 1 more Smart Citation
“…We appreciate Dongelmans et al 1 for their comments and the opportunity for clarification and further discussion. The beneficial findings of our study 2 are indeed beyond expectation but not contradictory to the current paradigm. Before end-of-therapy, finite-group patients had also enjoyed the benefits of the current paradigm, including immune restoration and reversal of hepatic fibrosis/cirrhosis during 1–5 years of nucleos(t)ide analog (Nuc) therapy 3 .…”
supporting
confidence: 46%
“…Accordingly, the finite group had lower end-of-follow-up HBsAg level (119 vs. 209.7 IU/mL, p <0.0001), more often <100 IU/mL (45.6 vs. 29.9%, p <0.0001) and a much higher 10-year HBsAg loss rate. The beneficial virtuous cycle of the greater HBsAg decline and the immune response elicited by HBV relapse after Nuc withdrawal was speculated as the driver for decreasing transcription of integrated HBV DNA toward HBsAg loss and reduction of hepatic carcinogenesis 2 . Certainly, HBsAg loss may contribute to the lower incidence of HCC, but a 10-year rate difference (22.3% vs. 2.9%) was not great enough to become a significant independent factor for HCC.…”
mentioning
confidence: 99%
“…We appreciate Deng et al 1 for their comments and the opportunity for clarification. To minimize bias, we set the end of nucleos(t)ide analog (Nuc) treatment (finite group) and 3-year-on-Nuc (continued group) as time 0 for propensity score matching 2 . This could be the best method second to randomized controlled trials.…”
mentioning
confidence: 99%
“…We have read with great interest the article by Jeng et al 1 in which they reported a decreased HCC risk and mortality rate in patients with cirrhosis who stopped nucleo(s)tide analog therapy compared with patients who continued nucleo(s)tide analog therapy. These findings are highly interesting and may provide new insights into the anticarcinogenic mechanisms in patients with chronic hepatitis B.…”
mentioning
confidence: 99%